Sustainability with Ecological and Economic Justice in China - Kin Chi, Lau (INTER DISCIPLINA, 2015)
Abstract | This paper examines the sustainability of China’s economic development since the 1979 Reform by addressing questions of socio-economic and ecological justice.It attempts to understand how the craze for Modernization entraps China in socio-economic injustices and aggravates environmental crises. It argues for adopting subaltern and ecological perspectives in challenging statist, elitist and anthropocentric discourses and practices concerning the question of sustainability in China.